PENGARUH PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATIONDAN DIRECT INSTRUCTION TERHADAPPENINGKATAN KEMAMPUAN PEMAHAMAN MATEMATISDITINJAUDARITINGKAT KEPERCAYAAN DIRI - Apsoh, Siti (2016)
Penelitianinibertujuanuntukmengetahuipengaruhpembelajarankooperatiftipe group investigationdandirect instructionterhadappeningkatan kemampuanpemahamanmatematisditinjaudaritingkatkepercayaandiri. Penelitianinimerupakanpenelitiankuasieksperimenyaitunon equivalent groups pretest-postest design.Subjekpenelitianiniadalahsiswa-siswikelas IVsalahsatuSekolahDasardi Palabuhanratu, KabupatenSukabumi.Instrumen yang digunakandalampenelitianiniadalahangketkepercayaandiri yang diberikansebelumpembelajaransebagaidasarpengelompokantingkatkepercayaandirisiswatinggi, sedangdanrendah. Selainituterdapatteskemampuanpemahamanmatematis yang diberikansebelumdansesudahpembelajaran.Hasildaripenelitianinimenunjukanbahwa(1) terdapatperbedaanpeningkatankemampuanpemahaman matematis antarasiswa yang belajardenganpembelajaran modelkooperatiftipe group investigationdan siswa yang belajardenganpembelajaranlangsung (direct instruction).(2) Terdapatperbedaankemampuanpemahaman matematis antarasiswa yang memiliki tingkat kepercayaan diri tinggi, sedang dan rendah.(3) Terdapatperbedaankemampuanpemahamanmatematisantarasiswaberkepercayaandiritinggi yang belajardengangroup investigation (GI)dandirect instruction (DI). (4) Terdapatperbedaankemampuanpemahamanmatematisantarasiswaberkepercayaandirisedang yang belajardengangroup investigation (GI) dan direct instruction (DI). (5) Terdapatperbedaankemampuanpemahamanmatematisantarasiswaberkepercayaandirirendah yang belajardengangroup investigation (GI) dan direct instruction (DI).(6) Tidakterdapatpengaruh interaksiantara model pembelajarandankepercayaandiriterhadapkemampuanpemahamanmatematis;-- The research aims to know the influence of cooperative learning; type group investigation and direct instruction to the improvement of mathematical comprehention ability based on the level of self confidence. This research was quasi eksperiment with nonequivalent group pretest and posttest design. The subject of this research was the students in grade 4 from one of the elementary schools in Palabuhanratu, Sukabumi regency. The instrument of the research was using questionnaire of self confidencis given before teaching learning process as the basic of grouping level of self confidence; high, medium, low level. Even there was a test of mathematical comprehension ability is given before and after teaching and learning process. The result of the research shows that (1) there is difference of improvement in mathematical comprehension ability between the students with the treatment by using cooperative learning; type group investigation and the students with the treatment by using direct instruction. (2) there is difference of mathematical comprehension ability between the students with the confidence of high, medium and low level. (3) there is difference of mathematical comprehension ability between the students with high self confidence level by using treatment of group investigation and the students with high self confidence level by using treatment of direct instruction. (4) there is difference of mathematical comprehension ability between the students with medium self confidence level by using treatment of group investigation and the students with medium self confidence level by using treatment of direct instruction. (5) there is difference of mathematical comprehension ability between the students with low self confidence level by using treatment of group investigation and the students with low self confidence level by using treatment of direct instruction. (6) there is no influence of interaction between learning model and the confidence to mathematical comprehension ability.